Pengembangan Budidaya Tanaman Holtikultura Organik Sebagai Salah Satu Atraksi Agrowisata Di Desa Lingsar - Sri Wahyulina; Sarifudin Sarifudin; Muhamad Akhyar; Embun Suryani (Universitas Mataram, 2022)
Lingsar Village is one of the villages in West Lombok Regency that has the potential to develop agro-tourism because 53% of its area consists of agricultural areas and fruit plantations. For this reason, Lingsar Village has great potential to develop organic horticultural plant cultivation which can be packaged as an agro-tourism attraction. This activity is expected to be one of the efforts to empower the community based on the creative economy and can contribute to increasing people's income. Currently, agricultural activities carried out by the people of Lingsar Village are only routine activities to plant on their land or land they rent. Agricultural activities in Lingsar Village are only carried out traditionally and conventionally so that they have not been able to have a significant impact on improving the welfare of the village community. For this reason, this activity aims to develop horticultural cultivation based on organic fertilizer with a touch of technology, which is then packaged so that it can become an agro-tourism attraction. The target to be achieved from this activity is the increasing capacity of the community to manage the potential of agro-tourism that is owned by being creative so that it can become an attraction for tourists. To achieve this target, the approach model used is Participatory Rural Appraisal (PRA) which emphasizes community involvement in all activities starting from planning, implementing and evaluating programs. This activity consists of three activities, namely counseling, demonstration plots (demonstration plots), and assistance in cultivating horticultural crops based on organic fertilizers and packaging them into agro-tourism attractions. The target group of this activity is the Millennial Farmer Group in Lingsar Village.